2021
DOI: 10.3389/fmicb.2021.686812
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation With Indigenous Rhizosphere Microbes Enhances Aboveground Accumulation of Lead in Salix integra Thunb. by Improving Transport Coefficients

Abstract: The application of plant–microbial remediation of heavy metals is restricted by the difficulty of exogenous microbes to form large populations and maintain their long-term remediation efficiency. We therefore investigated the effects of inoculation with indigenous heavy-metal-tolerant rhizosphere microbes on phytoremediation of lead (Pb) by Salix integra. We measured plant physiological indexes and soil Pb bioavailability and conducted widespread targeted metabolome analysis of strains to better understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 90 publications
0
10
0
1
Order By: Relevance
“…This study also identified 410 metabolites, which mainly constituted organic acids, amino acids and carbohydrates, in response to microbial inoculation. Further, around half of the identified metabolites were associated with HM bioavailability (Niu et al, 2021), thereby corroborating the role of microbes in increasing the phytoremediation efficiency. In another recent report, metabolomics and proteomics approach was used to study the mechanism of enhanced tolerance of wheat to Cd and Pd stress on inoculation with Enterobacter bugandensis TJ6 strain, a HM-immobilizing bacterium (Han et al, 2021).…”
Section: Metabolomicsmentioning
confidence: 54%
See 3 more Smart Citations
“…This study also identified 410 metabolites, which mainly constituted organic acids, amino acids and carbohydrates, in response to microbial inoculation. Further, around half of the identified metabolites were associated with HM bioavailability (Niu et al, 2021), thereby corroborating the role of microbes in increasing the phytoremediation efficiency. In another recent report, metabolomics and proteomics approach was used to study the mechanism of enhanced tolerance of wheat to Cd and Pd stress on inoculation with Enterobacter bugandensis TJ6 strain, a HM-immobilizing bacterium (Han et al, 2021).…”
Section: Metabolomicsmentioning
confidence: 54%
“…Inoculation with Pb-resistant Bacillus sp. and Aspergillus niger, showed enhanced proline levels as well as increased superoxide dismutase and catalase (antioxidants) activity (Niu et al, 2021). This study also identified 410 metabolites, which mainly constituted organic acids, amino acids and carbohydrates, in response to microbial inoculation.…”
Section: Metabolomicsmentioning
confidence: 73%
See 2 more Smart Citations
“…Soil microorganisms, such as Bacillus sp. and Aspergillus niger were confirmed to enhance antioxidant defenses of Salix and promote HMs bioavailability and improve transport coefficients finally (Niu et al 2021). As a HMs remediation tree species, Salix has high tolerance and accumulation capacity for HMs.…”
Section: Effect Of Bbc and Flooding On Phytoremediation Capacity Of S...mentioning
confidence: 99%